Development and design of the Ateneo Library Women's Writing information retrieval system (AIRS) - Bautista, Marie Edelquin D.; Olgado, Benedict S.; Lagrama, Eimee Rhea C. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Archives are kept by numerous archival facilities since it contains permanent and historical value. Organizing and providing access to these archives are two different important issues that needed a careful consideration. Currently, organization and classification are evenly implemented by the archival institutions with the help of the available archival standards. However, providing easy access to these archives, especially in the Philippines, is still a struggle with most of the archival facilities. One of which is the Ateneo Library of Women's Writings or ALiWW: an archival facility that was established in the year 1994. Currently, there is a need to provide an easy access to the ALiWW collection in order to increase its utilization and awareness in the community it belongs.
Therefore, this project aims to improve the utilization of ALiWW's archival collection by developing an information retrieval system that will facilitate an easy retrieval of archival materials. The AIRS or ALiWW's Information Retrieval System was developed as an answer to the low utilization of the ALiWW's archival collection. It enables users to search the entire collection of ALiWW by the title, name of a person, year, or any topics using keywords / advance keywords.
As the AIRS was implemented in the ALiWW reading room, different ALiWW users gave their evaluation in order to assess the effectiveness and efficiency of having this kind of system. The result of the evaluation shows that a high percentage of respondents agree that AIRS had effectively accomplished its purpose. Using the AIRS as a new method to access the ALiWW collection provides better quality services that reinforce in fulfilling the instructional and research activities of the Ateneo community. Additionally, it serves as a recognition to the ALiWW women donors.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Information retrieval system; Ateneo Library Women's Writing